2020–2021 Vegetable Production Handbook: Chapter 13. Pepper Production - Nathan S. Boyd; Eugene J. McAvoy; Christian F. Miller; Johan Desaeger; Gary E. Vallad; Phillip B. Williams; Peter J. Dittmar (EDIS)
This 33-page fact sheet is chapter 13 of the 2020–2021 Vegetable Production Handbook. Written by Nathan S. Boyd, Eugene J. McAvoy, Christian F. Miller, Johan Desaeger, Gary E. Vallad, and Phillip B. Williams, and published by the Horticultural Sciences Department, April 2020.